Interatomic Coulombic Decay Processes after Multiple Valence Excitations in Ne Clusters. (August 2015) - Iablonskyi, D; Nagaya, K; Fukuzawa, H; Motomura, K; Kumagai, Y; Mondal, S; Tachibana, T; Takanashi, T; Nishiyama, T; Matsunami, K; Johnsson, P; Piseri, P; et al.
Synopsis: We present a comprehensive analysis of autoionization processes in Ne clusters ( 5000 atoms) after multiple valence excitations by free electron laser radiation. The evolution from 2-body interatomic Coulombic decay (ICD) to 3-body ICD is demonstrated when changing from surface to bulk Frenkel exciton excitation. Super Coster-Kronig type 2-body ICD is observed at Wannier exciton which quenches the main ICD channel.